Analisis Permasalahan dan Solusi dalam Pembelajaran Tahfidz Qur'an Madrasah Ibtidaiyah Terpadu Tahfidzul Qur'an Al Ma'shum - Kinesti, Rakanita Dyah Ayu; Azkha, Millaty; Amali, Muhammad Fahris; Lathifah, Lisa Umi (Lembaga Yasin AlSys, 2023)
The purpose of this study is to explore the Learning of Tahfidz Qur'an in Kuttab class and regular class: analysis of problems and solutions of students of MI Terpadu Tahfizhul Qur'an Al-Ma'shum (MITTQUM), so that we can take knowledge and values aplus and then we apply. In this article using field research type research (field research). Descriptive qualitative approaches are used. For data collection techniques using observation, interviews, and documentation techniques, the researchers' interviews involved teachers and students. The documentation that the researchers took was in the form of photos of the classroom environment, school halls, and also children when memorizing This study also explains the problems and solutions of MI Terpadu Tahfizhul Qur'an Al-Ma'shum (MITTQUM) students. In MITTQUM there is a division of classes into two, namely the Regular class and the Kuttab class and also has 5 methods in its superior program, namely the wahdah, tallaqi, kitabah, sima'i, and juz'I methods. For the wahdah method is applied to students who are able to read the Qur'an well and have memorized a lot. Tallaqi is commonly applied to halaqoh. The kitabah method is applied to students with the status below, namely teaching writing and grub conditioning. Sima'i is applied every day in the school environment by rotating the murotal recitation of the Qur'an in the MI environment. For juz'i for students with good acceleration, namely students with good memorization. This MI also prioritizes collaboration with guardians, teachers who have a spirit of ihlas, high enthusiasm in teaching, and in the end children's problems can be minimized, and are able to encourage student learning well.